O coordenador pedagógico e o analfabetismo entre adolescentes escolarizados - Oliveira, Aline Gianoni de (2018)
The illiteracy issue among people who were exposed to teaching offered to school, but who have not benefited from it is little explored in academic research, although its relevance is unquestionable. Aiming to improve the discussion about this subject this work takes as the object of investigation the role of the pedagogical coordinator concerning the issue of illiteracy among schooled adolescents, trying to comprehend how this organizes, guides and implements the continuous training of teachers who teach from 6th grade to 9th grade. To obtain the data, this study, from qualitative basis, used as a methodological technique the focus group with participation of five General Pedagogical Coordinators (GCP) of the São Paulo state education network (SEESP) of schools of the Integral Education Program (PEI) of the south-central region of the city of São Paulo. The analysis and discussion of the data, made in the light of theoretical contributions on initial reading instructions, literacy and pedagogical coordination, indicated that they lack specific training on literacy to ensure the jointly planning actions against functional illiteracy described at schools they work. Speech of this professionals, shows the annoyance generated by the findings of your limitations against this sorrowful scenario and desires to obtain more theoretical and methodological knowledge to confront the problem. Although they indicate real possibilities of work inside the school with alternative places to encourage writing and reading of students, the proposition of formative actions in this sense, with integration and participation of teachers of all disciplines reveal themselves fragile. However, the reflexive process required by this research allowed to glimpse an initial formative plan in literacy to the pedagogical coordinator of Ending Years from elementary school